Privacy Preservation in Big Data - Prashanthi, M; Siva Kumar, AP (International Journal of Computer Sciences and Engineering, 2025)
As of late, enormous info has switched into a hot analysis theme. The expanding resolution of immense information builds the shot of breaking the safety of people. Since enormous info needs high calculation ability and intensive stockpiling, use distributed frameworks. As different gatherings are enclosed in these frameworks, the danger of security violation is expanded. Many securities safeguarding systems are created at information era, information stockpile and information handling levels of huge info life cycle. Protection conservation parts with large info and the difficulties for existing instruments are the prevailing goals. Specifically, we represent the new framework for securing immense info named ring signature. Moreover safeguarding modules in every section of the large fact life chain. In this, the file will be encrypted and stored in the cloud storage. If the attackers get the decryption key, the privacy of the file will be violated. And the integrity of the file not guaranteed. The file should be securely shared inside the group of the user without outsiders' inference. Besides, we speak the difficulties and future analysis directions determined with security in big data.